Physiological and Fitness Adaptations after Eight Weeks of High-Intensity Functional Training in Physically Inactive Adults - Matthew F. Brisebois; Brandon R. Rigby; David L. Nichols (MDPI AG, 2018)
The purpose of this study was to characterize high-intensity functional training (HIFT) in physically inactive adults. Four men and 10 women who were inexperienced with HIFT and not performing regular physical activity performed HIFT 3 days/week for 8 weeks. Health and fitness measures were assessed before and after the intervention. Resting heart rate (73 ± 12 vs. 68 ± 11 bpm) and resting diastolic blood pressure (71 ± 7 vs. 65 ± 6 mmHg) were reduced, while resting systolic blood pressure remained unchanged. Absolute VO2max (2.53 ± 0.68 vs. 2.69 ± 0.66 L/min) and relative VO2max (32.51 ± 8.84 vs. 34.31 ± 8.63 mL/kg/min) were improved. Lean body mass (48.20 ± 13.37 vs. 49.26 ± 13.81 kg) was increased, but fat mass was unchanged. Performance on the leg press (164.61 ± 54.35 vs. 201.62 ± 67.50 kg), bench press (39.12 ± 20.15 vs. 46.43 ± 21.18 kg), YMCA bench press (26 ± 13 vs. 37 ± 16 reps), one-minute sit-up (25 ± 9 vs. 32 ± 10 reps), and sit-and-reach (30.36 ± 11.36 vs. 32.14 ± 9.66 cm) were all increased. High-intensity functional training may be useful for improving health-related physical fitness parameters in physically inactive adults.